Landscape-Scale Wetland Restoration to Mitigate Dust Storms in Contemporary Uzbekistan - Satibaldieva, Nigora (The Lingua Spectrum, 2025)
The desiccation of the Aral Sea has transformed 5.5 million ha of former seabed into the planet’s newest salt desert, generating more than 100 sand-and-salt storms each year that blanket Northwest Uzbekistan and neighbouring countries. Since 2018 the government has pledged to stabilise this toxic surface through afforestation and wetland-creation campaigns, yet scientific assessments of their efficiency remain fragmented. This narrative review integrates peer-reviewed studies, government white papers and multilateral project reports (2015–2025) on large-scale rewetting and vegetative restoration of the Aralkum Desert. Particular attention is given to hydrologic engineering of artificial lagoons, the use of drought-resistant halophytes (Haloxylon aphyllum, Salsola richteri) and institutional innovations such as the 2024 “Green Seabed” decree. By synthesising ecological, socio-economic and linguistic research – including Uzbek-language terminology work published in The Lingua Spectrum – the article identifies evidence-based guidelines for dust-storm mitigation, habitat recovery and community co-benefits under a warming, water-scarce climate.